2018
DOI: 10.1016/j.ejvs.2018.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Asymptomatic Carotid Artery Stenosis in Patients Undergoing Coronary Artery Bypass Grafting

Abstract: https://clinicaltrials.gov. Unique identifier: NCT02319083.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…If ICA stenosis is left untreated, the risk of perioperative stroke in asymptomatic patients grows with stenosis severity and is highest among those with subtotal or bilateral stenosis. 2,3,32 The benefit of 'prophylactic' ICA revascularization preceding cardiac surgery in asymptomatic patients is still not well proven, and according to the current guidelines it might be considered in selected cases only. 15 Owing to some experts' opinions, however, it is reasonable to perform carotid revascularization in asymptomatic ICA stenosis ⩾ 80%, not only for perioperative stroke prevention, but also for long-term prognosis, and experienced centres should prefer CAS staged with CABG because of the lower MI rate.…”
Section: Discussionmentioning
confidence: 99%
“…If ICA stenosis is left untreated, the risk of perioperative stroke in asymptomatic patients grows with stenosis severity and is highest among those with subtotal or bilateral stenosis. 2,3,32 The benefit of 'prophylactic' ICA revascularization preceding cardiac surgery in asymptomatic patients is still not well proven, and according to the current guidelines it might be considered in selected cases only. 15 Owing to some experts' opinions, however, it is reasonable to perform carotid revascularization in asymptomatic ICA stenosis ⩾ 80%, not only for perioperative stroke prevention, but also for long-term prognosis, and experienced centres should prefer CAS staged with CABG because of the lower MI rate.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age, prior cerebrovascular disease/stroke, severity of carotid artery stenosis and peripheral vascular disease, presence of contralateral carotid occlusion and porcelain ascending aorta, postoperative IABP or ECMO supporting, unstable angina, urgency of the procedure, prolonged cardiopulmonary bypass time and postoperative atrial fibrillations were reported as the most consistent independent predictors of perioperative stroke after CABG (7,41,42) . Gender, diabetes mellitus, hypertension, prior myocardial infarction, chronic renal failure and congestive heart failure showed contradictive results (7) .…”
Section: What Are the Predictors Associated With Stroke After Cabg?mentioning
confidence: 96%
“…Also, patients who described a history of stroke were significantly more likely (OR=3.6) to have further stroke than those who were asymptomatic (4) . Santarpino et al (7) reported that among 649 patients with asymptomatic carotid artery stenosis >50% undergoing isolated CABG, the incidence of postoperative stroke was 1.5% and the risk of stroke were significant only in patients with a stenosis ³90% (OR=12, CI=1.4-33.3). They concluded as asymptomatic, severe carotid artery stenosis has a low prevalence and when left untreated is associated with a relatively low risk of postoperative stroke.…”
Section: Does Untreated Asymptomatic Carotid Stenosis Was Associated mentioning
confidence: 99%
See 1 more Smart Citation
“…Mehta et al demonstrated that both asymptomatic unilateral and bilateral carotid stenoses were independent risk factors for in-hospital stroke after CABG 11 . However, other investigations have suggested that routine preoperative screening for asymptomatic carotid artery disease in CABG patients does not translate into reduced perioperative stroke risk and is likely not justified 12,13 . Some institutions continue to perform routine carotid artery ultrasound screening prior to CABG in order to identify significant carotid arterial disease that may require revascularization before or during CABG with the assumption that carotid disease is causally related to perioperative stroke and that prophylactic carotid revascularization may decrease the risk for post-CABG neurologic events.…”
Section: Coexisting Coronary and Carotid Artery Diseasementioning
confidence: 99%